2019
DOI: 10.1108/sampj-12-2017-0156
|View full text |Cite
|
Sign up to set email alerts
|

Is integrated reporting transformative?

Abstract: Purpose This paper aims to generate insights about the transformative potential of integrated reporting by exploring organisational adoption of non-financial reporting design archetypes available in the field. Design/methodology/approach Drawing on the concept of design archetype, this study conducts an exploratory interpretative based on qualitative semi-structured interviews and documentary analysis. The study is based on the Spanish integrated reporting field. Findings This study reveals that IIRC frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 53 publications
1
22
0
2
Order By: Relevance
“…Although there was an abundance of information available internally, much of the nonfinancial information was collated manually using spreadsheets, as there was no ability for the internal accounting system to manage it. This is a common problem with IR (SAICA, 2015;Rodríguez-Gutiérrez et al, 2019), and as there is no existing mainstream accounting system currently available to deal with this issue (Stroehle and Rama Murthy, 2019), this study demonstrates that it is likely to continue to be a constraint in the successful adoption of IR and integrated thinking. In this case, not only did it provide challenges for internal Management control systems reporting and accountability but also the potential to reduce the buy-in from middle managers if they started to doubt the non-financial metric choices.…”
Section: Constraining Controlsmentioning
confidence: 85%
“…Although there was an abundance of information available internally, much of the nonfinancial information was collated manually using spreadsheets, as there was no ability for the internal accounting system to manage it. This is a common problem with IR (SAICA, 2015;Rodríguez-Gutiérrez et al, 2019), and as there is no existing mainstream accounting system currently available to deal with this issue (Stroehle and Rama Murthy, 2019), this study demonstrates that it is likely to continue to be a constraint in the successful adoption of IR and integrated thinking. In this case, not only did it provide challenges for internal Management control systems reporting and accountability but also the potential to reduce the buy-in from middle managers if they started to doubt the non-financial metric choices.…”
Section: Constraining Controlsmentioning
confidence: 85%
“…Among them, and consistently with the emancipatory ethos of the social accounting project within the SEA literature (Gray, 2002), several papers follow an action research approach, as they argue that this method enables researchers not only to observe but also to contribute to the development of the potential changes that SAR can drive (Adams & McNicholas, 2007; Mitchell et al, 2012). However, most studies draw on case studies (Contrafatto & Burns, 2013; Le Breton & Aggeri, 2019; Leong & Hazelton, 2019; Li & Belal, 2018) or qualitative interviewing (Albelda-Pérez et al, 2007; Rodríguez-Gutiérrez et al, 2019; Stubbs & Higgins, 2014) as their empirical methods. Methods where the researcher has a less interventionist role, such as questionnaires (Arjaliès & Mundy, 2013), discourse analysis (Tregidga et al, 2014), or thematic content analysis (Maroun, 2018), are also applied.…”
Section: Mapping the Literature On Sustainability Accounting And Repo...mentioning
confidence: 99%
“…The distinction between different organizational structures and orders of change allow various studies to observe that SAR can change organizations’ design archetypes (i.e., the structures and practices that provide coherence to organizations) but not their interpretative schemes (i.e., the DNA or the core beliefs and values that are imprinted in the organization; see Larrinaga & Bebbington, 2001; Maroun, 2018; Stubbs & Higgins, 2014). Indeed, SAR can be conceived as an emergent design archetype, a set of new practices embodying the values and beliefs of alternative interpretative schemes (Narayanan & Adams, 2017; Rodríguez-Gutiérrez et al, 2019) and, consequently, its implementation generates some change. For example, Gunarathne and Lee (2015) report that changes in environmental management accounting promote environmental integration, thereby fostering further developments in environmental management accounting practices.…”
Section: Mapping the Literature On Sustainability Accounting And Repo...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, Larrinaga and Bebbington (2001) highlighted the way in which structural modifications of organizational behavior are accompanied by a change in rationality. More recently, Narayanan and Adams (2017) and Rodríguez-Gutiérrez et al (2019) studied the effects of social and environmental accounting on organizational changes. They showed that a lack of transformative capacity can even constitute an environmental disruption to the practice of business reporting.…”
Section: Theoretical Backgroundmentioning
confidence: 99%